2023
DOI: 10.1002/mrc.5372
|View full text |Cite
|
Sign up to set email alerts
|

Automated identification and quantification of metabolites in human fecal extracts by nuclear magnetic resonance spectroscopy

Abstract: We report the development of a software program, called MagMet‐F, that automates the processing and quantification of 1D 1H NMR of human fecal extracts. To optimize the program, we identified 82 potential fecal metabolites using 1D 1H NMR of six human fecal extracts using manual profiling and a literature review of known fecal metabolites. We acquired pure versions of those metabolites and then acquired their 1D 1H NMR spectra at 700 MHz to generate a fecal metabolite spectral library for MagMet‐F. The fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Optimization of MagMet for Wine Profiling. After identifying 70 reliably measurable wine compounds through manual profiling, we then determined if our earlier versions of MagMet 37,38 could correctly process the wine NMR spectra. We found that the original MagMet could indeed process wine spectra but needed slight modifications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimization of MagMet for Wine Profiling. After identifying 70 reliably measurable wine compounds through manual profiling, we then determined if our earlier versions of MagMet 37,38 could correctly process the wine NMR spectra. We found that the original MagMet could indeed process wine spectra but needed slight modifications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Each wine sample was prepared for NMR analysis following the standard procedures for MagMet. 37,38 However, for wine samples, some steps may be best performed with some minor methodological alterations (detailed in the Results and Discussion section). Initially, 0.5 mL of each sample was filtered through a thoroughly prewashed Amicon 3 kDa MWCO centrifugal filter.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the manual quantification of analytes in NMR spectra has been a tedious, slow, user-dependent process requiring a trained spectroscopist with domain knowledge of the analytes. Semi-automated and automated software have been developed for metabolite profiling from NMR data (e.g., Chenomx, Magmet, and LipSpin) [ 5 , 6 ]; however, these techniques are slower and less scalable compared to processing using neural networks (NNs). Despite past approaches described in the literature [ 7 , 8 ] and the current surge of interest in artificial intelligence (AI), NNs have yet to gain traction in the realm of targeted NMR profiling.…”
Section: Introductionmentioning
confidence: 99%